ANALISIS KUALITAS PELAYANAN DI BALAI PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BP3TKI) SEMARANG PROVINSI JAWA TENGAH - Prakerti, Galeh; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
BP3TKI Semarang is one Unit located in Central Java. KTKLN manufacture services have established procedures to obtain KTKLN, satisfaction CTKI / TKI will service KTKLN manufacture can be fulfilled. KTKLN-making services are still not as expected CTKI / workers. This can be seen from several things, among others: the online system used often trobel, queue numbers available does not guarantee CTKI / TKI directly dilayanani. For the waiting room available in BP3TKI also inadequate. Employees are less vigilant attitude, and competent in providing services. This study aims to: 1) How is the quality of service manufacture BP3TKI KTKLN in Semarang? 2) what are the factors that cause the quality of service to less well in the service BP3TKI KTKLN in Semarang? The study states: Quality of Service contained in Semarang BP3TKI less maximal, it is seen in: 1) The procedure was appropriate service standards of service, but the procedure is too long and should be simplified. 2) Suitability period given to the products CTKI / migrant workers in the service KTKLN are in accordance with the needs. However, the card can not be extended, making it less effective and efficient. 3) online monitoring tool can make a solution for the repair or continuous improvement, but because it has not applied to make less good. 4) product in the form of smart card services are free of damage but it is not free from errors in typing, but can be said is good because it rarely happens. 5) The need CTKI / migrant workers in terms of information contained in BP3TKI Semarang has been good, but there is no other information provided there, such as the cost of insurance information, or information about CTKI / other migrant workers. 6) Design services available has been good, but the facilities need to be supported by good physical infrastructure that makes CTKI / TKI feel comfortable. Dimensions cause menajadi poor service quality can be seen below: 1) Facility located in BP3TKI less good, because inadequate. 2) skills possessed by each officer has been good, but needs to be balanced with extensive knowledge. 3) Responsiveness of employees in giving attention to the applicant has been good because in accordance with what is expected by the applicant. 4) Warranty service is good, timeliness of service, and also manufacture KTKLN is free of charge. 5) Empathy care workers is not good, because there are still complaints coming from CTKI / TKI.